2019
DOI: 10.3389/fimmu.2019.00540
|View full text |Cite
|
Sign up to set email alerts
|

Brain Citrullination Patterns and T Cell Reactivity of Cerebrospinal Fluid-Derived CD4+ T Cells in Multiple Sclerosis

Abstract: Immune responses to citrullinated peptides have been described in autoimmune diseases like rheumatoid arthritis (RA) and multiple sclerosis (MS). We investigated the post-translational modification (PTM), arginine to citrulline, in brain tissue of MS patients and controls (C) by proteomics and subsequently the cellular immune response of cerebrospinal fluid (CSF)-infiltrating T cells to citrullinated and unmodified peptides of myelin basic protein (MBP). Using specifically adapted tissue extraction- and combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 55 publications
0
28
0
Order By: Relevance
“…Detailed exploration into the target proteins of PAD-mediated deimination in COVID-19 will need further assessment, as the subcellular distribution of deiminated proteins is tissue type-dependent [ 108 ]. The citrullinome of chronic diseases has been reported, including rheumatoid arthritis (RA), multiple sclerosis (MS) and Alzheimer’s disease (AD) [ 82 , 109 , 110 ], as well as in a range of taxa throughout the phylogenetic tree, both in plasma and the EV secretome [ 39 , 44 , 45 , 46 , 47 , 48 , 66 , 67 , 111 ]. Interestingly, the enrichment of deiminated proteins for KEGG pathways relating to viral infection has recently been identified in the serum and serum EVs of alligator and cow, both which are animals with unusual anti-viral responses [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Detailed exploration into the target proteins of PAD-mediated deimination in COVID-19 will need further assessment, as the subcellular distribution of deiminated proteins is tissue type-dependent [ 108 ]. The citrullinome of chronic diseases has been reported, including rheumatoid arthritis (RA), multiple sclerosis (MS) and Alzheimer’s disease (AD) [ 82 , 109 , 110 ], as well as in a range of taxa throughout the phylogenetic tree, both in plasma and the EV secretome [ 39 , 44 , 45 , 46 , 47 , 48 , 66 , 67 , 111 ]. Interestingly, the enrichment of deiminated proteins for KEGG pathways relating to viral infection has recently been identified in the serum and serum EVs of alligator and cow, both which are animals with unusual anti-viral responses [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The three α-helical regions of the GFAP central rod domain are indicated by boxes separated by nonhelical linker regions, and the N-terminal head and C-terminal tail domains are indicated by straight lines. Amino acids identified as sites of citrullination are shown in red ( Jin et al., 2013 ; Brenner and Nicholas, 2017 ; Faigle et al., 2019 ), sites of phosphorylation are shown in blue ( Inagaki et al., 1994 ; Battaglia et al., 2019 ), and the single site for lipoxidation is shown in green ( Viedma-Poyatos et al., 2018 ). Evidence also exists for N-glycosylation and O-glycosylation of GFAP, but none of the specific sites for these modifications is known ( Kanninen et al., 2004 ; Korolainen et al., 2005 ).…”
Section: Structurementioning
confidence: 99%
“…Citrullination, the enzymatic conversion of peptidyl-arginine to peptidyl-citrulline through deimination, is another posttranslational modification of potential significance (reviewed in Brenner and Nicholas, 2017 ). Citrullination has been observed at multiple arginine residues in neurologically normal individuals ( Jin et al., 2013 ; Faigle et al., 2019 ); both the number of sites and/or amount increases in several diseases, including multiple sclerosis ( Nicholas et al., 2004 ; Faigle et al., 2019 ), experimental allergic encephalomyelitis ( Nicholas et al., 2005 ), Alzheimer’s disease ( Ishigami et al., 2005 , 2015 ), and hepatic fibrosis ( Kim et al., 2018b ). In vitro studies have suggested that citrullination interferes with GFAP polymerization ( Inagaki et al., 1989 ).…”
Section: Structurementioning
confidence: 99%
“…A larger amount of PADI2 is localized in the periaxonal regions, which could explain why this end of the oligodendrocyte is the first to undergo to apoptosis [ 76 ]. However, it appears that citrullination of MBP has a limited role in activating T lymphocytes, and, therefore, unlikely to play a role in the development of MS [ 77 ]. Therefore, the role of citrullination of MBP in the pathogenesis of MS remains unclear.…”
Section: Epigenetic Mechanisms Of Regulation Of Herv-w Expressionmentioning
confidence: 99%